Optimasi Proses Sales Invoice Melalui Implementasi Software di PT Swabina Gatra Travel - Hardi, Ilham; Anwar, Muhadjir (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this activity is to be able to know the application of Jurnal.id accounting software in facilitating a job, especially in the field of financial preparation, especially sales invoices, as well as obstacles as a user in using this technology. The counseling was conducted using lecture, question and answer, demonstration, and hands-on practice methods. The result of this activity is that the production of sales invoices generated using Jurnal.id software can facilitate the finance department in obtaining clear and effective reports. Information needs are needed in accordance with company expectations when making decisions on existing problems. Jurnal.id software that is implemented is adequate in processing existing data and has quality information quality, but there are often obstacles in using this software due to errors in recording transactions on the system. The conclusion of this activity is that Jurnal.id software can facilitate users in the process of recording transactions so as to produce a sales invoice that can help when making decisions